2019
DOI: 10.1002/aqc.3061
|View full text |Cite
|
Sign up to set email alerts
|

The decline of short‐beaked common dolphin (Delphinus delphis) in the waters off the island of Ischia (Gulf of Naples, Italy)

Abstract: 1. This study presents data on a local population of short-beaked common dolphin monitored in the waters off Ischia Island (Gulf of Naples, Italy) over a 16-year period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). We examine dolphin occurrence and distribution and perform photoidentification analysis.2. The data presented support the hypothesis that the waters around Ischia Island represent a feeding area, as well as a calving and an important nursery area f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…Estimations of encounter rate, group size, density, and abundance values of D. delphis were made by the application of CDS analysis to sighting data collected during standardized surveys carried out near Samos Island, Greece (Eastern Aegean Sea), providing a comparison with analogous values estimated in similar studies carried out in other Mediterranean areas ( Table 3). The encounter rates estimated in the study area were higher than values reported for the Alborán Sea [4], in waters off Ischia Island [14], in the Inner Ionian Sea Archipelago [6,32], and in the Thracian Sea [35], indicating that the waters off the south of Samos Island are an eligible habitat for D. delphis. The estimated ER values could be used as an effective baseline for future assessment of the common dolphin conservation status in the area, where an increasing trend in small-scale fishery exploitation and tourist flow have been recorded in the last few years, representing potential harmful threats for the species.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Estimations of encounter rate, group size, density, and abundance values of D. delphis were made by the application of CDS analysis to sighting data collected during standardized surveys carried out near Samos Island, Greece (Eastern Aegean Sea), providing a comparison with analogous values estimated in similar studies carried out in other Mediterranean areas ( Table 3). The encounter rates estimated in the study area were higher than values reported for the Alborán Sea [4], in waters off Ischia Island [14], in the Inner Ionian Sea Archipelago [6,32], and in the Thracian Sea [35], indicating that the waters off the south of Samos Island are an eligible habitat for D. delphis. The estimated ER values could be used as an effective baseline for future assessment of the common dolphin conservation status in the area, where an increasing trend in small-scale fishery exploitation and tourist flow have been recorded in the last few years, representing potential harmful threats for the species.…”
Section: Discussioncontrasting
confidence: 68%
“…The small-sized aggregation of common dolphin groups is probably due to a behavioral feeding strategy caused by the distribution of prey (small pelagic fish) over many small patches in the study area [5,28,54], which leads dolphins to split into smaller groups for more efficient predation [55]. On the other hand, the presence of highly productive marine areas and the high seasonal abundance of prey leads to the formation of larger groups of D. delphis as observed in the western Alborán and southern Almeria [4,11], in the Tyrrhenian Sea [8,13,14] and in waters off Malta Island [31]. Indeed, the presence of small pelagic fish such as sardine and anchovy resulted in an important explanatory variable in the modelling of the distribution of the common dolphin as reported by the authors of [28] in the Aegean Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter suggests a complex social network in a fission-fusion social structure, possibly reflecting local ecological characteristics (unpredictable and patchy prey distribution; Bruno et al, 2004). In the Tyrrhenian Sea, however, several individuals formed lasting associations, and a core of 12 females T A B L E 1 Common dolphin photo-identification, mark-recapture and social structure studies in the Mediterranean Sea was sighted together nine times in five different years (Mussi et al, 2021). This preferred companionship indicated durable social patterns and strong association levels among females at different reproductive states (females from late pregnancy to the first year of their calves' life; females from early pregnancy to parturition of their calves and the period thereafter; females with older calves or without calves).…”
Section: Photo-identification and Social Structurementioning
confidence: 99%
“…Further dietary analysis using stable isotopes on common dolphin tissues sampled from the same region proposed that individuals are weaned at up to 150 cm in length (Giménez et al, 2017). In the NE Atlantic, studies have indicated that weaning may commence between 3 and 6 months after birth (Brophy, Murphy, & Rogan, 2009), though some individuals may not be fully weaned until around 10 months of age (Murphy, 2004), which is equivalent to approximately 140 cm in body length (Murphy & Rogan, 2006), and the length of lactation period may increase with maternal age (Murphy et al, 2013 Bearzi, Bonizzoni, Santostasi, Furey, et al (2016) for Gulf of Corinth (also IMMA); ( 4) Milani et al (2017Milani et al ( , 2019 for North Aegean waters; (5) Mussi & Miragliuolo (2003 and Mussi et al (2021) for waters of Ischia Island (also IMMA); ( 6) Vella ( 2005), Vella (2015), and for Central Mediterranean waters around the Maltese Islands; ( 7) Bearzi et al (2003) and Pace et al (2015) in southern part of the Pelagos Sanctuary; (8) Cañadas and Hammond (2008) and Giménez, Cañadas, et al (2018) for the Alboran Sea (also IMMA); (9) Gómez de Segura et al (2006Segura et al ( , 2007 Alegro-Provencal basin analyses. However, from the strandings in the North Aegean Sea recorded between 2000 and 2013 (Milani C, et al, 2000(Milani C, et al, -2013Milani et al, 2017), it was possible to obtain body length measurements for three females, nine males, and four unsexed common dolphin specimens, which ranged in size between 106 cm and 240 cm with an average body length of 203 cm (n = 16) and an SD of 31.4 cm.…”
Section: Life History and Body Sizementioning
confidence: 99%